Systematic analysis of brain and skull ischemic injury expression profiles reveals associations of the tumor immune microenvironment and cell death with ischemic stroke - Zhang, Chao; Wang, Lisi; Guo, Yunmiao; Feng, Wei (Frontiers in Immunology, 2022)
Background Previous studies have shown that stroke is a potential first sign of neoplasia, but the relationship between stroke and cancer remains unclear. As a complex brain disease, ischemic stroke involves cell death and immunity. Thus, it is necessary to investigate the association of the tumor immune microenvironment and cell death with ischemic stroke. Methods We established a photothrombosis-induced ischemic injury model in mouse brain and skull. Subsequently, we sequenced the whole transcriptome of the injured mouse brain and skull and analyzed the expression profiles. To investigate the association of stroke with cell death and cancer, we systematically performed gene set enrichment analysis in pan-cell death (i.e., apoptosis, cuproptosis, ferroptosis, necroptosis, and pyroptosis) and the cancer hallmark pathways. The time-dependent immune cell abundance variations after ischemic injury were estimated. Furthermore, pan-cancer genomic and prognostic analyses of the ischemic injury-related gene sets were also performed. Results In this study, we found that there exist temporal and spatial differences in the gene expression patterns of both the brain and skull with ischemic injury. The skull ischemic injury-induced changes in the brain transcriptome were particularly great, but could recover in a short period, while the skull transcriptome variation resulting from brain ischemic injury was long-lasting. In addition, the expression of the genes related to ischemic injury was also associated with pan-cell death and the cancer hallmark pathways. The changes in the abundance of immune cells indicate that brain ischemic injury may disrupt the immune microenvironment for a longer time, while the skull can balance the stability of the immune microenvironment better. Moreover, the brain ischemic injury-related gene sets were highly correlated with a variety of tumors, particularly glioblastoma multiforme (GBM), kidney renal clear cell carcinoma (KIRC), brain lower grade glioma (LGG), and uveal melanoma (UVM), which carry a greater mortality risk after stroke. Conclusion This systematic analysis not only helps in the understanding of the changes in the gene expression profiles of both the brain and skull with ischemic injury but also reveals the association of the tumor immune microenvironment and cell death with ischemic stroke.